THE ESSENCE OF DEATH AS THE EVOLUTION OF THE SOUL INTERTEXT STUDY IN HINDU LITERATURE - Nengah Sumantra; A.A Made Arsana Putra (Perkumpulan Organisasi Profesi DPP Dosen Hindu Indonesia (DHI) Bekerja sama dengan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar dan Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
Every religion teaches about the truth, which can be practiced by its people in this life. This truth they believe can keep them from all kinds of suffering. Hindu belief about life after death, it can be seen from the literary works that can be heard from the general public there are similarities with Islam, namely the Al-Sirat bridge, but in Bali this bridge is called Titi-Ugal-Agil¬. The bridge (titi) can also move to make it difficult for those who during their life did evil to cross it. With the explanation above, death in Hinduism is not the end of life, because in Hindu belief life will continue from the previous life until death. According to Hinduism, death and life will continue to occur over and over again (Punarbawa) until a person reaches his final destination which is Moksha. Based on this background, three problems can be formulated, namely (1) Why do people experience the process of death according to Hindu literature? (2) How is the journey of the atman/soul after experiencing the process of death, according to Hindu literature? (3) How does the law of karma affect the process of death in Hindu literature? The purpose of this study is to add to the literature as a reference that can support Hindus to have a clear knowledge of the essence of the soul's journey after death. The method used is data collection, literature, and observation. The theories used in this research are the theory of religion (religion), the theory of intertextuality, the theory of hermeneutics, and the theory of change. The results of this study can enrich the literature on Hindu religious teachings related to death. Death is a common thing for every living being, in this world everyone who is born into the world will surely experience death in the future. Heaven and Hell we can feel in this world (when we are reborn). The goal of Hinduism is not Heaven, but moksha. In essence, death has an impact on the Law of Karma which includes: psychological, religious, socio-cultural and social impacts.